2018
DOI: 10.1029/2018jd029231
|View full text |Cite
|
Sign up to set email alerts
|

Source Sector Attribution of CO2 Emissions Using an Urban CO/CO2 Bayesian Inversion System

Abstract: We assimilate multiple trace gas species within a single high-resolution Bayesian inversion system to optimize CO 2 ff emissions for individual source sectors. Starting with carbon monoxide (CO), an atmospheric trace gas with fairly well-known emissions, we use emission factors of CO and CO 2 ff (called R CO ) defined for each source sector to enable us to jointly use CO and CO 2 atmospheric mole fractions to constrain CO 2 ff sectoral emissions. We first show that our combined CO-CO 2 inversion is theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Bottom-up emissions from the Hestia CO 2 emission product 21,32 are available for each of the eight economic sectors, merged into two main sectors of emissions 27 corresponding to low (referred to as stationary incl. residential, industrial, commercial, utility, airport, and railroad sectors) and high (ref to as mobile incl.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Bottom-up emissions from the Hestia CO 2 emission product 21,32 are available for each of the eight economic sectors, merged into two main sectors of emissions 27 corresponding to low (referred to as stationary incl. residential, industrial, commercial, utility, airport, and railroad sectors) and high (ref to as mobile incl.…”
Section: ■ Methodsmentioning
confidence: 99%
“…A model-measurement error of 2 ppm was assigned to each three-hourly CO 2 mole fractions, similar to previous network designs for South Africa (Nickless et al, 2015(Nickless et al, , 2018b and Australia (Ziehn et al, 2014), and used in previous regional CO 2 inversions (Nathan et al, 2018). Following Ganesan et al 2015, we assigned modelmeasurement error uncertainties to each three-hourly CH 4 and N 2 O mole fraction observation of 10 ppb and 0.4 ppb, respectively.…”
Section: Model-measurement Error Covariance Matrixmentioning
confidence: 99%
“…As the urban population is expected to increase by 2.5 to 6 billion people in 2050, anthropogenic CO 2 emissions are projected to increase dramatically, especially in developing regions and countries (Sargent et al, 2018;Ribeiro et al, 2019). Under such a scenario, the observations of atmospheric CO 2 and 13 C-CO 2 in urban landscapes are of great importance to monitoring these potential CO 2 emissions hotspots (Lauvaux et al, 2016;Nathan et al, 2018;Graven et al, 2018;Pillai et al, 2016;Staufer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…By using CO 2 observations, the "top-down" atmospheric inversion approach is a useful tool to evaluate "bottom-up" inventories (Graven et al, 2018;L. Hu et al, 2019;Lauvaux et al, 2016;Nathan et al, 2018). Previous research has shown that additional information, such as data on atmospheric 14 CO 2 -CO 2 , 13 C-CO 2 , and CO, is needed to better distinguish CO 2 emissions from different sources and to assess their uncertainties (Chen et al, 2017;Graven et al, 2018;Nathan et al, 2018;Cui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation